Design and Psychometric Properties of a Self-Care Questionnaire for the Elderly - Masomeh Hemmati Maslak Pak; Leila Hashemlo (Sālmand, 2015)
Objectives: The purpose of this study was to design an Iranian cultural adaptable questionnaire for the assessment of self-care in the elderly.